PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PERPAJAKAN DALAM UNDANG-UNDANG PERPAJAKAN DI KANTOR WILAYAH DIREKTORAT JENDERAL PAJAK RIAU DAN KEPULAUAN RIAU - Nurfazilah, Rani; Indra, Mexsasai; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Law enforcement is a series of efforts, processes and activities to make the law apply as it should. Tax is seen as very important in a welfare state that is as an income to improve the social welfare of the people in the country. But in reality in Indonesian society in general, often there are criminal acts in the field of taxation in the form of negligence and intentionality, both by the taxpayer itself. So that there is a loss of state financial revenue that comes from taxes. The purpose of writing this thesis is First to find out the law enforcement conducted by the Directorate General of Tax of Riau and Riau Islands against the perpetrators of taxation crimes in Riau. Secondly, to find out the factors that cause taxpayers to commit taxation crimes at the Directorate General of Tax Riau and Riau Islands. Third, to find out the obstacles faced by the Directorate General of Tax Riau and Riau Islands in carrying out the enforcement of taxation criminal law by taxpayers.From the results of research conducted there are three main things that can be concluded. First, law enforcement in the field of taxation in general has not been optimal and implemented as expected. Because in the implementation of taxation criminal law enforcement prioritizes tax criminal law which is ultimum remedium meaning criminal acts as a last resort if previous efforts such as appeals, coaching then inspection of taxpayer compliance is not ignored. Second, there are several factors that cause taxpayers to commit taxation crimes, especially factors from humans themselves. Third, there are several obstacles and must be resolved faced by the Directorate General of Tax, Riau and Riau Islands, in carrying out enforcement of taxation criminal acts by taxpayers.Keywords: Law Enforcement-Tax-Tax Crime